Exploration of The Magnetic Rocks Potential of Mount Penanggungan: A Study of Myth, History, and Its Implications for Educators and Mountaineers - Iqbal Ainur Rizki; Eko Hariyono; Muhammad Nurul Fahmi; Madlazim; Eka Puji Astuti; Muhammad Eka Abdul Ghofar; Luthfi Aryani (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
This study explores the potential of magnetic stones on Mount Penanggungan and their relation to history and myths circulating in the community and climbers. This research is important to do in order to minimize the rate of injury caused by fatigue for climbers on this mountain. In addition, aspects of physics and history can be implications for educators to deliver material on the subject. This research uses a qualitative design with the type of case study—data collection methods through observation, interviews, and document studies. The results of this study show that some rocks on Mount Penanggungan, especially when approaching their peak, have a magnetic field anomaly up to 4 times larger than the magnetic field on the earth’s surface, characterized by its darker color or cave walls. Based on the mythical and historical review, the role of magnetic stones underlies the reason ancient people performed hermitage on rocks and in Mount Penanggungan. This study implies that it can be information for climbers that rocks with a strong magnetic field magnitude can accelerate the relaxation of the body. In addition, educators can integrate this research’s findings, including physical phenomena and historical/mythical aspects on Mount Penanggungan, into learning.